The Concept of Ihsan in Islamic Religious Education as the Foundation of Public Service in the Era of Digital Government: Penelitian - Rahman, Aulia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Digital government transformation requires a strong ethical foundation to ensure public services that are not only efficient but also moral. This study analyzes the concept of Ihsan in Islamic Religious Education as a philosophical basis for public services in the digital era through library research using a thematic analysis approach. The findings show that the concept of Ihsan has evolved in meaning from a ritual-spiritual dimension to a holistic paradigm that is relevant to the demands of contemporary digital services. The integration of Ihsan values requires multidimensional transformation at the individual, institutional, and systemic levels, including character building among civil servants, organizational culture development, and a supportive policy framework. Trustworthiness in Ihsan-based digital services manifests itself in transparency, accountability, and responsiveness driven by moral-spiritual awareness. Implementation in the context of Society 5.0 requires a balanced approach between technological optimization and the preservation of human values. The research produced an integrative theoretical model consisting of five synergistic components: Spiritual Foundation, Ethical Governance, Technology Optimization, Human Development, and Social Impact as a comprehensive and sustainable implementation framework in the development of ethical digital government.